2012
DOI: 10.1371/journal.pone.0048074
|View full text |Cite
|
Sign up to set email alerts
|

MRI Assessment of Lumbar Intervertebral Disc Degeneration with Lumbar Degenerative Disease Using the Pfirrmann Grading Systems

Abstract: BackgroundTo evaluate by MRI intervertebral disc degeneration in patients with lumbar degenerative disease using the Pfirrmann grading system and to determine whether Modic changes correlated with the Pfirrmann grades and modified Pfirrmann grades of disc degeneration.MethodsThe clinical data of 108 surgical patients with lumbar degenerative disease were reviewed and their preoperative MR images were analyzed. Disc degeneration was evaluated using the Pfirrmann grading system. Patients were followed up and low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 25 publications
2
75
1
2
Order By: Relevance
“…Finally, despite the fact that some studies have demonstrated a positive correlation between the presence of Modic changes and the degree of disc degeneration as measured by the Pfirrmann scale [1,57], we found that the combination of Modic changes and the degree of disc degeneration significantly enhanced the strength of the newly proposed score, and L5/S1 levels (a). No degenerative endplate changes were observed in both levels.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…Finally, despite the fact that some studies have demonstrated a positive correlation between the presence of Modic changes and the degree of disc degeneration as measured by the Pfirrmann scale [1,57], we found that the combination of Modic changes and the degree of disc degeneration significantly enhanced the strength of the newly proposed score, and L5/S1 levels (a). No degenerative endplate changes were observed in both levels.…”
Section: Discussioncontrasting
confidence: 78%
“…2). As recent studies have demonstrated no significant correlation between different Modic types and surgical outcomes [57], in the present study we chose to group together Modic type 1 and Modic type 2 changes.…”
Section: Methodsmentioning
confidence: 99%
“…We used a modified Pfirrmann grading system,[20] which divides IVD degeneration into four grades, according to NP signal intensity, homogeneity, and loss of disc height (Table 1). A board-certified radiologist and a spine fellow analyzed the MR images.…”
Section: Methodsmentioning
confidence: 99%
“…In the presented study, the NP voxel count of punctured IVDs was correlated to established outcome measures for this rat-tail model: disc height measurements using X-rays[19], qualitative MR imaging based on the modified Pffirmann scale[20] and histological assessments according to the grading system developed by Han B. [15]…”
Section: Introductionmentioning
confidence: 99%
“…Inflammatory changes that closely correlate with disc degeneration and are occasionally seen in vertebral endplates, i.e. Modic magnetic resonance imaging (MRI) changes, are also believed to be the possible source of low back pain 38 .…”
Section: Spinal Degeneration Instability and Painmentioning
confidence: 99%